2008
DOI: 10.1007/s12160-008-9024-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Frequency Moderates the Effects of Message Framing on HPV Vaccine Acceptability

Abstract: This study provides an important exception to the commonly observed gain-framed advantage for preventive health behaviors. Loss-framed appeals appear to be particularly effective in promoting interest in low-frequency prevention behaviors such as HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 35 publications
(84 reference statements)
4
90
2
Order By: Relevance
“…Similarly, lossframed information has been found to be more persuasive than gain-framed information for recipients who perceive the behaviour as relatively effortless (Gerend, Shepherd, & Monday, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, lossframed information has been found to be more persuasive than gain-framed information for recipients who perceive the behaviour as relatively effortless (Gerend, Shepherd, & Monday, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Message content was identical across conditions; only the frame and color differed. Messages were modeled after previous research (Gerend & Shepherd, 2007;Gerend et al, 2008). See Table 1 for excerpts.…”
Section: Methodsmentioning
confidence: 99%
“…When considering a new vaccine, therefore, an individual may be more responsive to a loss-framed message because people tend to be more willing to take risks (i.e., receive a new vaccine) when faced with losses than with gains. Indeed, recent evidence suggests that, under certain circumstances-particularly circumstances that amplify the salience of threat-loss-framed messages are more persuasive than gain-framed messages in promoting interest in vaccination (Gerend & Shepherd, 2007;Gerend, Shepherd, & Monday, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Sometimes clear non-support does not do the trick: when one study found an overall loss-framed advantage for vaccination behaviour, clearly and unequivocally a prevention behaviour, the authors did not overtly question the tenets of the risk-framing hypothesis, instead describing the results as 'an important exception to the commonly observed gain-framed advantage for preventive health behaviours' (Gerend, Shepherd, & Monday, 2008;p. 221).…”
Section: The Use Of Additional Hypothesesmentioning
confidence: 99%